Synergistic Effects of Trichoderma harzianum, 1,3 Dichloropropene and Organic Matter in Controlling the Root-Knot Nematode Meloidogyne incognita on Tomato - Giada d’Errico; Nicola Greco; Francesco Vinale; Roberta Marra; Virgilio Stillittano; Salvatore Walter Davino; Sheridan Lois Woo; Trifone D’Addabbo (Plants, 2022)
Environmental concerns raised by synthetic nematicides are encouraging integrated management strategies based on their combination with non-chemical control tools, such as biocontrol agents and/or organic amendments. In this study, the combination of the fumigant 1,3-dichloropropene (1,3-D) with a commercial formulation of the biocontrol agent Trichoderma harzianum (TH) and an organic fertilizer (OF) was investigated in two consecutive tomato crops for its effect on the root-knot nematode Meloidogyne incognita and plant growth and yield. The application of 1,3-D was only performed on the first crop, while TH and OF were provided to both crops. Almost all treatments significantly reduced nematode infestation in both crops, though the greatest nematicidal effect was caused by a combination of the three products. The treatment with 1,3-D limited its nematicidal efficacy to the first crop only. Fumigant integration with TH and OF also resulted in the greatest increases of plant growth and yield. Therefore, the integrated management of root-knot nematodes with a soil fumigant, a bionematicide as T. harzianum and a source of organic matter demonstrated effective nematode suppression though limiting the number of chemical applications.